CONTRIBUTION OF JEWISH MINORITY TO THE ECONOMIC DEVELOPMENT OF BACAU - Filipoaia, Cristina-Iolanda; Deju, Mihai (Studies and Scientific Researches. Economics Edition, 2020)
During more than six centuries of existence, Bacău benefited both from the favourable socio-economic and political context, and from the interrelationships with the other communities, from the harmonious combination of these two elements resulting both the growth and development of the locality and the position in the local and regional hierarchy. The main beneficiaries of the progress made were of course the inhabitants, the city representing a living environment for them, as well as the essential factor in the functional dynamics and in the urban landscape. Giving meaning to the past, we must recognize that each community that contributed to the development of Bacău has its own history, Bacău becoming the trustee of the communities ‘history entirety, which in perfect communion with Romanians defined the complex identity of the locality. The Jewish community is no exception, whose collaboration with Romanians for over two centuries has contributed to increasing the economic level of development of the locality since the second half of the 18th century.